IMPROVING STUDENTS’ READING COMPREHENSION ON NARRATIVE TEXT BY USING STORY MAP - Meliza Nesia Shari; Endang Susilawati; Urai Salam (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract:This research answer the problem that is the use of story map reading strategy improves students reading comprehension on narrative text of the second years student of SMPN 10 Singkawang. This research is intended to answer the problem to investigate how well story map improves students’ ability in mentioning the detail information from the generic structure and language feature of narrative text. The researsch method used in this research is the clasroom action research method. The writer used observation checklist table and field note as the tool of data collection. On the first, second and third cycle, the writer used kinds of interesting material and teaching media, such as pictures, vocabulary preparation to encourage the students’ involvement in the teaching learning process. The mean score in the first cycle was 57,5 in the second cycle was 62,4; and in the third cycle was 70,3. Based on Story Map Strategy,the students’ ability in reading comprehension on narrative text evidently improves. Keyword : Reading comprehension, Narrative text, Story Map